HUBUNGAN PELAYANAN PRIMA TERHADAP KEPUASAAN PASIEN RAWAT JALAN DI PUSKESMAS DOLOK MASIHUL TAHUN 2021 - Diana Sinulingga; Saiful Batubara; Alprindo Sembiring; Akhmad Fatikhus (Jurnal Penelitian Kesmasy, 2021)
Excellent service at public health Dolok Masihul is not as expected due to the partent family’s dissatisfaction about the doctor’s attitude in responding to the patient’s complaint, the attention of the doctor and the nurse when the patient complains about the illness staffered is still lacking, the action is less rapid in doing the treatment to the patient, The accountability for completing tasks is not timely and no good communication exists between doctor, nurse and patient. Excellent service in review of six dimensions that are Attitude, appearance, attention, action, accountability, and abilitity. This study aimedto determine the relationship between excellent service with outpatient satisfaction in publich health center dolok masihul. The research type was quantitative, with cross sectional method, 96 samples were taken with purposive sampling technique, The statistical test used clu-squera (a=0,05) with the following test result : attitude (P=0,003) < a ( 0.05), appearance (P=0.000< a (0.05), attention (P=0.012) < a (0.05), action (P=0.026) < a (0.05), accountability (P=0.009) < a (0.05), ability (P=0.0037) < a ( 0.05), on outpatient unit of public health Dolok masihul. The conclusion of this research is the satisfaction of outpatient patient at Dolok masihul Puskesmas will increase if attitude, appearance, attention, actin, responsibility and ability are improved. Efforts should be made to improve the attitude of friendliness, mastery of therapeutic communication, customer service, improve the discipline of all employees including doctors.